2017
DOI: 10.1136/bcr-2016-218269
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal alloimmune thrombocytopaenia associated with maternal HLA antibodies

Abstract: Neonatal alloimmune thrombocytopaenia (NAIT) generally results from platelet opsonisation by maternal antibodies against fetal platelet antigens inherited from the infant's father. Newborn monochorionic twins presented with petechial haemorrhages at 10 hours of life, along with severe thrombocytopaenia. Despite the initial treatment with platelet transfusions and intravenous immunoglobulin, they both had persistent thrombocytopaenia during their first 45 days of life. Class I human leucocyte antigen (HLA) anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A major limitation of these studies, involving unselected pregnant women, was the very low number or even absence of thrombocytopenic newborns. Despite the negative findings observed in unselected pregnant women, numerous case reports have been published in which neonatal thrombocytopenia, occasionally accompanied by severe bleeding complications, occurred in women with anti‐HLA class I antibodies (Svejgaard et al , ; Sternbach et al , ; Evans, ; Chow et al , ; Onishi et al , ; del Rosario et al , ; Sasaki et al , ; Tanaka et al , ; Saito et al , ; Moncharmont et al , ; Thude et al , ; Gramatges et al , ; Starcevic et al , ; Hutchinson et al , ; Nakamura et al , ; Meler et al , ; Wendel et al , ). The authors suggested a causal relationship between maternal anti‐HLA antibodies and foetal or neonatal disease.…”
mentioning
confidence: 99%
“…A major limitation of these studies, involving unselected pregnant women, was the very low number or even absence of thrombocytopenic newborns. Despite the negative findings observed in unselected pregnant women, numerous case reports have been published in which neonatal thrombocytopenia, occasionally accompanied by severe bleeding complications, occurred in women with anti‐HLA class I antibodies (Svejgaard et al , ; Sternbach et al , ; Evans, ; Chow et al , ; Onishi et al , ; del Rosario et al , ; Sasaki et al , ; Tanaka et al , ; Saito et al , ; Moncharmont et al , ; Thude et al , ; Gramatges et al , ; Starcevic et al , ; Hutchinson et al , ; Nakamura et al , ; Meler et al , ; Wendel et al , ). The authors suggested a causal relationship between maternal anti‐HLA antibodies and foetal or neonatal disease.…”
mentioning
confidence: 99%
“…NAIT is caused by maternal immunoglobulin G alloantibodies that cross the placenta and are directed against HPAs on fetal platelets [ 7 ]. While the HPA antigens frequently involve maternal alloantibodies against HPA, human leucocyte antigen (HLA) antibody binding to platelets is a rare cause of NAIT [ 8 ]. In the fetal blood, the alloantibodies attack the platelet surfaces, as mentioned above, and neonatal thrombocytopenia ensues [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports about anti-HLA antibody binding to platelets and cause FNAIT have also been published [57,58]. Studies concluded that the presence of anti-HLA class I antibodies should be considered as a potential cause of NAIT, especially in cases with a very high titter of antibodies.…”
Section: Foetal/neonatal Alloimmune Thrombocytopaeniamentioning
confidence: 99%